Integrasi Nilai-Nilai Keislaman dalam Profesionalisme Guru di Lembaga Berbasis Islam di TK Islam Terpadu Bumi Bahari - Renawati Renawati; Miftakhul Jannah; Wan Della Septriasa (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
In early childhood education, teachers serve not only as educators but also as role models in shaping character and spirituality. At Islamic institutions such as TK Islam Terpadu Bumi Bahari, the integration of Islamic values into teacher professionalism is essential to investigate. This article aims to analyze how Islamic values are incorporated into teachers’ attitudes and professional competencies, and how this contributes to educational quality. Using a descriptive qualitative method through observation and documentation, it was found that practices such as routine worship, moral-based learning, and the instillation of Islamic values in daily routines significantly enhance teacher professionalism. Observations revealed that teachers not only deliver academic content but also guide students spiritually through activities such as Quran recitation, dhuha prayer, and storytelling about Islamic teachings. This indicates that teacher professionalism is inseparable from the Islamic educational mission. These findings highlight the necessity of teacher competency development that aligns holistically with Islamic values.